2018
DOI: 10.54366/jdr.11.2.2018.18-24
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Working Capital Management on Profitability of Indian Company

Abstract: Liquidity and profitability are both the two different sides of same coin. Optimum level of Working capital Management plays an important role liquidity guarantees a firm to meet their shortin any business organization. It reveals the term debts and the proper management of flow management's efficiency of decision making can be promised by a profitable business. regarding short-term financing need of the business. Liquidity shows the ability of company in Corporate finance literature and finance practitioners … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
3
0
0
Order By: Relevance
“…Should there be a spike in the ICP, the companies’ profitability will suffer dramatically. These are similar results found in the study (Chand et al, 2019; Mahato & Jagnnathan, 2016). In model 4, the coefficient of FA and FS is negative and significant, depicting the inverse relationship between FA and FS and ROE.…”
Section: Empirical Analysissupporting
confidence: 92%
See 2 more Smart Citations
“…Should there be a spike in the ICP, the companies’ profitability will suffer dramatically. These are similar results found in the study (Chand et al, 2019; Mahato & Jagnnathan, 2016). In model 4, the coefficient of FA and FS is negative and significant, depicting the inverse relationship between FA and FS and ROE.…”
Section: Empirical Analysissupporting
confidence: 92%
“…The fact that the coefficient of CCC in model 4 has a negative value and is substantial indicates that it has an inverse relationship with ROE; this means that if the CCC is raised, the company’s profitability will drop by a sizeable amount. Similar results were also found in the study (Chand et al, 2019; Mahato & Jagnnathan, 2016; Makori & Jagongo, 2013). Although the coefficient of FA and FS is significant and negative in model 4, it represents an inverse relationship with ROE.…”
Section: Empirical Analysissupporting
confidence: 89%
See 1 more Smart Citation
“…IHP assists a manager in controlling the risk of 'stock-outs' and periodic sales, which help to improve customer demand and decrease ordering carrying costs. The research studies of Singh, Kumar, and Colombage (2017) [50] ; Mahato et al (2016) [32] ; Vartak et al (2019) [58] ; (Lampty et al, (2017) [28] and Samiloglu et al (2016) [46] found a negative relationship between IHP and profitability. But, the studies by Simon et al (2019); Amponsah-Kwatiah et al (2020) [10] ; Zeidan et al (2017) [60] ; and.…”
Section: Inventory Holding Period (Ihp)mentioning
confidence: 99%
“…"Working Capital Management" (WCM) refers to the choices an organization makes about its short-term investments and financing, which can affect a corporation's liquidity. The terms "current assets" and "current liabilities" are included in the definition of components of working Capital (Mahato and Jagannathan, 2016;Naskar and Guha, 2016;Boruah, 2020; Yadav and Singh, 2020) [46, 21, 58,] . Current assets include things like cash, accounts receivable, and inventories.…”
Section: Introductionmentioning
confidence: 99%